If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + (a + 3) + (a + -5) = 76 Reorder the terms: a + (3 + a) + (a + -5) = 76 Remove parenthesis around (3 + a) a + 3 + a + (a + -5) = 76 Reorder the terms: a + 3 + a + (-5 + a) = 76 Remove parenthesis around (-5 + a) a + 3 + a + -5 + a = 76 Reorder the terms: 3 + -5 + a + a + a = 76 Combine like terms: 3 + -5 = -2 -2 + a + a + a = 76 Combine like terms: a + a = 2a -2 + 2a + a = 76 Combine like terms: 2a + a = 3a -2 + 3a = 76 Solving -2 + 3a = 76 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3a = 76 + 2 Combine like terms: -2 + 2 = 0 0 + 3a = 76 + 2 3a = 76 + 2 Combine like terms: 76 + 2 = 78 3a = 78 Divide each side by '3'. a = 26 Simplifying a = 26
| y+x=63 | | 5.1x-18=48.3 | | 0.70x=1 | | -4(x+12)=-60 | | 0.85x=1 | | 54x+3(x+30)+(x+30)*4+50=3493 | | T=7-3n | | 2*x-2*x=0 | | 6x-18 = 6 | | 2/×=10/15 | | 2*x-2*y=0 | | x-(x*0.325)=1870 | | x-(x*0.16)=1784 | | 20=14-2(5a+w) | | 168=16t^2+32t | | (7x+3)=(4x-5x+6) | | 2x^4-13x^3+28x^2-23x+6=0 | | 12x+-89+53=204 | | C=2(a-b) | | 40x+105-75=190 | | an-5an-1+6an-2=1 | | 40xsomething+105-75=190 | | (1.04)n=13 | | 11+8r=29 | | 183+12-x+5=175 | | 45-(5x+8)=5(x+3)+x | | 1-3(2)=7 | | -(2x-4)=22 | | x-3(2)=7 | | 2x+8x-10=0 | | Ln(x)=0.21 | | lnx=0.21 |